Characterization of New Molecular Markers of Three Botflies Parasitizing Cervid Hosts. Issue 3 (4th February 2021) - de la Fuente, Ana M; Caparrós, Noelia; Mora-Rodríguez, José M; Molina, María; Aleix-Mata, Gaël; Velarde, Roser; Fidalgo, Luis E; López-Beceiro, Ana M; Lorite, Pedro; Boos, Mathieu; Faure, Eva; Pérez, Jesús M; et al.
Abstract: Specific identification of oestrid larvae is usually problematic not only when using morphobiometric features, but also when applying molecular criteria, since very few molecular markers have been described for this group of flies. New molecular markers for oestrid are needed for more reliable species identification, diagnostic purposes, and epidemiological surveys; moreover, they can help in phylogenetic reconstruction. Here, we report the characterization of COI, 28S rDNA, ITS1, and ITS2 in Cephenemyia stimulator from roe deer and in Cephenemyia auribarbis and Pharyngomyia picta from red deer. The COI and 28S rDNA are very uniform in length, while the ITSs sequences are highly variable at both intraspecific and interspecific levels. The described ITSs sequences were longer than those described for other dipteran species by the presence of simple repeats and tandem repeat sequences. In C. auribarbis both ITS1 and ITS2 appeared as two variants, one short and the other long. In general, the analyzed markers present low intraspecific genetic variation and high interspecific variation. ITSs showed the greatest amount of intraspecific and interspecific variation. Phylogenetic analysis demonstrated that the characterized sequences differentiate the species and genera of Oestridae.